Effect of naftidrofuryl on the metabolic response to surgery. Issue 6283 (4th July 1981) - Burns, H J; Galloway, D J; Ledingham, I M
Abstract : In a randomised study of 34 patients undergoing elective operations of moderate severity naftidrofuryl infusion significantly improved postoperative nitrogen balance. The control group excreted 26.2 +/- 2.7 g nitrogen in the first three postoperative days. A group treated with naftidrofuryl excreted 18.0 +/- 1.6 g nitrogen in the same period (p less than 0.0005). The preoperative nutritional state of patients treated with naftidrofuryl did not differ from that of the controls. Though hormonal changes causing an improvement in nitrogen balance could not be excluded by this study, the results show that naftidrofuryl infusion may stimulate postoperative catabolism of endogenous carbohydrate and fat, thus sparing tissue protein.